Significance of CD Markers in the Classification, Patterns and Sub Typing of Non Hodgkin’s Lymphoma (Medical Forum Monthly, 2024)
Objective: Aim of this study is Immunohistochemical analysis of H&E diagnosed cases of NHL for confirmation, classification and differentiation on the basis of phenotypic expression of CD3, CD30, CD45 and CD20 markers.Study Design: Prospective study.Place and Duration of Study: This study was conducted in the Pathology department of Liaquat University of Medical and Health Sciences Jamshoro (LUMHS) during October 2010 to March 2012Materials and Methods: The sample consisted of all the specimens received in the Pathology department of Liaquat University of Medical and Health Sciences Jamshoro (LUMHS) during the above period. Immunohistochemical stains including CD3, CD30, CD20 and CD45 were used for classification and differentiation of cases of NHL.Results: Out of one hundred and eighty (180) H & E diagnosed cases of Non Hodgkins Lymphoma, only 142 (78.8%) were positive for CD20 and were confirmed as B cell NHL; however 6 (3.3%) cases showed positivity with CD30 and were confirmed as large T-cell NHL. 38(21.2%) cases showed positivity for CD3 and all 180 (100%) cases were positive for CD45 and were confirmed as NHL.Conclusion: It is concluded that Immunohistochemistry is helpful in differentiation of NHL. Cases of B cell NHL occur more frequently than T cell NHL. Furthermore NHL is more common in males and mostly presents with nodal involvement.